Molecular Mechanism of Local Drug Delivery with Paclitaxel-Eluting Membranes in Biliary and Pancreatic Cancer: New Application for an Old Drug - Sookhee Bang; Sung Ill Jang; Su Yeon Lee; Yi-Yong Baek; Jieun Yun; Soo Jin Oh; Chang Woo Lee; Eun Ae Jo; Kun Na; Sugeun Yang; Don Haeng Lee; Dong Ki Lee (Gastroenterology Research and Practice)
Implantation of self-expanding metal stents (SEMS) is palliation for patients suffering from inoperable malignant obstructions associated with biliary and pancreatic cancers. Chemotherapeutic agent-eluting stents have been developed because SEMS are susceptible to occlusion by tumor in-growth. We reported recently that paclitaxel-eluting SEMS provide enhanced local drug delivery in an animal model. However, little is known about the molecular mechanisms by which paclitaxel-eluting stents attenuate tumor growth. We investigated the signal transduction pathways underlying the antiproliferative effects of a paclitaxel-eluting membrane (PEM) implanted in pancreatic/cholangiocarcinoma tumor bearing nude mice. Molecular and cellular alterations were analyzed in the PEM-implanted pancreatic/cholangiocarcinoma xenograft tumors by Western blot, immunoprecipitation, and immunofluorescence. The quantities of paclitaxel released into the tumor and plasma were determined by liquid chromatography-tandem mass spectroscopy. Paclitaxel from the PEM and its diffusion into the tumor inhibited angiogenesis, which involved suppression of mammalian target of rapamycin (mTOR) through regulation of hypoxia inducible factor (HIF-1) and increased apoptosis. Moreover, implantation of the PEM inhibited tumor-stromal interaction-related expression of proteins such as CD44, SPARC, matrix metalloproteinase-2, and vimentin. Local delivery of paclitaxel from a PEM inhibited growth of pancreatic/cholangiocarcinoma tumors in nude mice by suppressing angiogenesis via the mTOR and inducing apoptosis signal pathway.